Services in the School Intensive Mental Health Program - Wahyu Aulizalsini; Hema Dayita (International Journal of Psychology and Health Science, 2026)
Student mental health is a crucial aspect that must be addressed because it directly impacts children's development across educational, social, and emotional spheres. Schools, as strategic environments, play a crucial role in providing comprehensive and sustainable mental health services. This study aims to examine various services within intensive school-based mental health programs. The method used was a literature review, analyzing relevant scientific journals related to school-based mental health services. The results indicate that services within intensive mental health programs include guidance and counseling, psychoeducation, social-emotional skills training, and the creation of a supportive school environment. The success of program implementation is influenced by resource factors, the role of guidance and counseling teachers, and stakeholder involvement. Therefore, several programs are needed to positively impact child development within the school environment. Implementing these programs requires the direct involvement of all school stakeholders, as thorough preparation and planning are essential, as well as adaptive school policies are essential for their success.